2018
DOI: 10.1123/jsep.2017-0267
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Explicit–Implicit Evaluative Discrepancy to Exercise Dropout in Middle-Aged Adults

Abstract: Discrepancies between automatically activated associations (i.e., implicit evaluations) and explicit evaluations of motives (measured with a questionnaire) could lead to greater information processing to resolve discrepancies or self-regulatory failures that may affect behavior. This research examined the relationship of health and appearance exercise-related explicit-implicit evaluative discrepancies, the interaction between implicit and explicit evaluations, and the combined value of explicit and implicit ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Also in the context of physical activity, it has been shown that IED exists and that it impacts behavior [33, 34]. For example, the lower IED was in a sample of fitness club exercisers, the more successful they were in achieving their ideal exercise frequency [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also in the context of physical activity, it has been shown that IED exists and that it impacts behavior [33, 34]. For example, the lower IED was in a sample of fitness club exercisers, the more successful they were in achieving their ideal exercise frequency [33].…”
mentioning
confidence: 99%
“…For example, the lower IED was in a sample of fitness club exercisers, the more successful they were in achieving their ideal exercise frequency [33]. In another study, discrepancy between explicit and implicit health measures regarding PA was negatively associated with the length to participate in a one year long exercise program [34]. These findings demonstrate that there is a direct link between IED and PA behavior.…”
mentioning
confidence: 99%
“…Other studies have shown a negative effect of (IED) on exercise behavior (7,10). In Berry and colleagues' study, greater (IED) was negatively related to the duration of exercise in one year (16).…”
Section: Introductionmentioning
confidence: 84%
“…For example, if one has somewhat undesirable automatic evaluations of Physical Activity (PA), but positive explicit evaluations, the evaluations might differentially in uence decisions to approach or avoid that occasion to be physically active (10). In one example of bodybuilding workouts, the ideal frequency of training increased with less (IED) (16). However, Chevance and colleagues concluded there is little empirical evidence yet regarding a real discrepancy amongst the implicit processes that regulate exercise (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the growing popularity of HCFC worldwide, and in Brazil in particular, these spaces have not received a great deal of attention from researchers investigating adherence, retention and dropout rates in PA programs, with most efforts in this field being concentrated on supervised interventions, randomized controlled trials, and established group exercise programs outside HCFC settings (Berry et al 2018, Kuehl et al 2016, Lorenz et al 2015. Alternatively, some research has looked at these rates within HCFC settings but from a marketing perspective, establishing satisfaction levels and intention to repurchase as some of the main variables to understand PA adherence as consumer behavior (Cañamero et al 2019, Gonçalves et al 2016, Hurley 2004.…”
Section: Introductionmentioning
confidence: 99%